Detection of beta-globin gene mutations in Malaysia: comparison between marms and FTH methods / Rusilawaty Abdullah - Abdullah, Rusilawaty (2015)
Beta thalassemia is one of the common inherited blood disorders worldwide. This disease occurred due to mutations such as substitution of nucleotide, frameshift mutation, minor deletions and rarely due to large major deletions. Nowadays, many techniques were applied for mutation analysis and multiplex-amplification refractory mutation system (MARMS) is an available method being used for diagnosis of common beta globin gene mutations, particularly in patients diagnosed in UKMMC. However, it is labor-intensive and time consuming especially when detecting numerous common beta-globin gene mutations. Recently, the flow-through hybridization (FTH) method was introduced. Thus, the aim of this study was to compare the detection of beta globin gene mutations using MARMS and FTH techniques in patients of UKMMC. A total of 100 samples of EDTA blood were obtained from patients diagnosed as thalassemia patients and were screened with MARMS. A total of 56 specimens screened by MARMS were chosen for FTH assay. From the 56 cases that were successfully detected by both methods, 40 samples had similar results for detection of mutations. In addition, the FTH assay managed to show 12 samples with additional mutations including the 45 Kb deletion, 619bp deletion, Cap+1 and Poly A. However, two samples were not detected in FTH but were detected with MARMS (Cd 8/9). For genotyping result, 43 samples were detected as heterozygous in FTH while 44 samples were reported as heterozygous in MARMS. The discrepancies observed were due to the primers not included in the respective assays. Hence, there is possibility of using FTH which is much simpler and rapid method for detection of vast common beta globin gene mutations.